Extrapulmonary small cell carcinoma of bone. Issue 796 (February 1992) - Raina, V.; Milroy, R.; al-Dawoud, A.; Dunlop, D.; Soukop, M.
Abstract : Small cell carcinoma has been reported to arise in many extrathoracic sites. However, such tumours arising from bone have not been previously described. We report what we believe is the first reported case of extrapulmonary small cell carcinoma of bone. The tumour arose from the fifth dorsal vertebra in a 60 year old woman. The patient was treated with local radiotherapy and combination chemotherapy and remains in remission, 18 months after diagnosis. As such extrathoracic small cell tumours are rare, there seem to be no clear-cut guidelines for treating them, but combination chemotherapy is recommended.